All You Need is Cable TV? - Iversen, Vegard; Palmer-Jones, Richard (Journal of Development Studies, 2019)
Robert Jensen and Emily Oster find that arrival of cable TV in rural India reduces women's tolerance of spousal violence, son preference and fertility, and increases women's autonomy, and school enrolment. These results are mostly replicated using their data and code. However, cable TV does not affect uneducated women. Theoretically informed index construction reduces the tolerance of violence effect, and weakens that on autonomy. We have statistical power concerns, and find errors and questionable assumptions in school enrolment constructions. Using our data constructions, effects sizes and significance are weakened. These results suggest that pure, statistical and scientific replication have merit.